In vitro toxicity of ceramic nanoparticles in 3D human airway epithelial cultures - Bessa, Maria João (2022)
This study aimed to investigate the in vitro toxicity of engineered (ENP) and airborne ceramic NP in a 3D human bronchial epithelial model (MucilAir™) under air-liquid interface conditions.